Study of the timber constructive systems that are more commercialized in Brazil - Bittencourt, R. M.; Ino, A. (R I L E M Publications, 1999)
The Brazilian houses in wood are executed with several techniques and species, in function of the areas they are located, therefore, it is treated of regional traditional houses, built practically without modem technological resources. These houses are the ones of the tropical areas, where there is abundance of this material, or the ones of the south region, prevailing the European immigrant's constructive techniques. Nowadays, in the urbanized centers of the country it is observed that this type of house can be found sheltering the most lacking populations, in the slums; or in highly sophisticated residential units which are conceived and executed by specialist professionals for a social class of high purchasing power; or still, those that are marketed by companies of small load, that offer standardized residences, usually acquired by the middle class as second residence, in the field or in the coast. The work has for objective to study the houses of these companies that are consolidated at the market, identifying the constructive system, the product; as well as, its production process, trying to verify which technologies are incorporated to these processes. The analysis that was made allows a larger understanding of the product, wood house, that exists in the market and identification of the technological degree in the productive process of those constructive systems.